An exploratory study on the usage of electronic medical records(EMR) among private clinics in Kuching, Sarawak / Suhaida Halamy... [et al.] - Halamy, Suhaida; Ismailly, Norlida; Hj. Bibi, Zainon (Universiti Teknologi Mara Cawangan Sarawak, 2010)
Most of healthcare centers that include the hospitals and clinics in the western countries already acknowledge the importance of implementing EMR to increase the efficiency and effectiveness of their services. In Malaysia, the use of EMR among hospitals and clinics is relatively low and there are very few study had been done about the trend of utilizing EMR in the country. In Sarawak in particular, it is unknown whether any study had been done to address this issue. This is one of the reasons that prompted us to carry out this study. As for the beginning, Kuching was chosen as it is the largest town in Sarawak with the most private clinics operating in city area. The purpose of this study is to examine the level of practices of EMR among private clinics in Kuching and the level acceptance and utilization of EMR among the clinicians and physicians.